T-cell receptor triggering is critically dependent on the dimensions of its peptide-MHC ligand. - Choudhuri, K; Wiseman, D; Brown, M; Gould, K; Van Der Merwe, P (2005)
The binding of a T-cell antigen receptor (TCR) to peptide antigen presented by major histocompatibility antigens (pMHC) on antigen-presenting cells (APCs) is a central event in adaptive immune responses. The mechanism by which TCR-pMHC ligation initiates signalling, a process termed TCR triggering, remains controversial. It has been proposed that TCR triggering is promoted by segregation at the T cell-APC interface of cell-surface molecules with small ectodomains (such as TCR-pMHC and accessory receptors) from molecules with large ectodomains (such as the receptor protein tyrosine phosphatases CD45 and CD148). Here we show that increasing the dimensions of the TCR-pMHC interaction by elongating the pMHC ectodomain greatly reduces TCR triggering without affecting TCR-pMHC ligation. A similar dependence on receptor-ligand complex dimensions was observed with artificial TCR-ligand systems that span the same dimensions as the TCR-pMHC complex. Interfaces between T cells and APCs expressing elongated pMHC showed an increased intermembrane separation distance and less depletion of CD45. These results show the importance of the small size of the TCR-pMHC complex and support a role for size-based segregation of cell-surface molecules in TCR triggering.